2013
DOI: 10.1088/0004-637x/779/1/57
|View full text |Cite
|
Sign up to set email alerts
|

SUZAKUOBSERVATIONS OF THE DIFFUSE X-RAY EMISSION ACROSS THE FERMI BUBBLES' EDGES

Abstract: We present Suzaku X-ray observations along two edge regions of the Fermi Bubbles, with eight 20 ks pointings across the northern part of the North Polar Spur (NPS) surrounding the north bubble and six across the southernmost edge of the south bubble. After removing compact X-ray features, diffuse X-ray emission is clearly detected and is well reproduced by a three-component spectral model consisting of unabsorbed thermal emission (temperature kT 0.1 keV) from the Local Bubble, absorbed kT 0.3 keV thermal emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
166
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(196 citation statements)
references
References 64 publications
23
166
2
Order By: Relevance
“…The ROSAT X-rays map at 1.5 keV shows limb brightening [4], which agrees also with the recent SUZAKU measurements at 0.3 keV [13]. The Xrays emission is most likely thermal bremsstrahlung, although a synchrotron component from very high-energy electrons cannot be neglected.…”
Section: Some Key Features Of the Fermi Bubblessupporting
confidence: 89%
“…The ROSAT X-rays map at 1.5 keV shows limb brightening [4], which agrees also with the recent SUZAKU measurements at 0.3 keV [13]. The Xrays emission is most likely thermal bremsstrahlung, although a synchrotron component from very high-energy electrons cannot be neglected.…”
Section: Some Key Features Of the Fermi Bubblessupporting
confidence: 89%
“…enhancement of temperature and density across the FB edge as observed by Kataoka et al (2013). Though we assume that the injection region is spherical symmetric, a departure from this assumption does not change the qualitative/quantitative picture much.…”
Section: Results: Wind and Bubble Morphologymentioning
confidence: 94%
“…The speed required to reach ∼ 10 kpc in 1 Myr is ∼ 10 4 km s −1 , achievable by relativistic jets slowed down by the hot circumgalactic medium (CGM). The power required for inflating young FBs is much higher and the outer shock is much stronger (Guo & Mathews 2012;Zubovas & Nayakshin 2012), and X-ray emissivity and temperature much higher than what is observed (Kataoka et al 2013). The SNe-driven models of FBs consider them to be long lived ( 10 Myr), and thus the injected power is smaller.…”
Section: Introductionmentioning
confidence: 93%
“…The N excess is possibly due, instead, either to local enrichment that occurred at a previous stage or to some non-local source associated with the hypershell model. Kataoka et al (2013) performed a large set of Suzaku observations crossing the northern and southern edges of the Fermi Bubbles, therefore probing several fields within the NPS. They found strong X-ray absorption, which was hardly explained with a local origin, but rather suggested that the NPS emission comes from gas associated with strong past activity of the Galactic Center.…”
Section: Introductionmentioning
confidence: 99%